Implementasi Nilai Dakwah Islamiyah Dalam Seni Wayang Golek Untuk Peningkatan Karakter Masyarakat - Mujahidin Amhar Wicaksana; Apri Wardana Ritonga; Ade Agustian; Kiki Dasuki (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
The massive spread of Islamic da'wah today is closely related to the media and methods used. One form of implementing Islamic da'wah is through the art of wayang golek as well as increasing the value of community character. This study will discuss the form of implementation of Islamic da'wah values in the art of wayang golek as well as its influence in increasing the value of community character. This study uses a descriptive analysis method from library sources in answering the problems that exist in this study. The research found and revealed that the process of implementing Islamic da'wah values through the media of wayang golek still has a big influence on efforts to improve character in society, because in one wayang golek play there are many aspects that can be studied starting from the value of monotheism, social criticism, and influence in people's lives. Of course, various aspects that are conveyed through wayang golek must also be an effort to adjust to the development of the times so that the value of Islamic da'wah conveyed through the media of wayang golek is right on target and in accordance with the mission of increasing community character values. Research on the implementation of Islamic da'wah values through wayang golek media also recommends further research to be carried out to increase understanding of Islamic da'wah values and increase the character values of society in this modernization era.